2023
DOI: 10.3389/fendo.2023.1160155
|View full text |Cite
|
Sign up to set email alerts
|

Impaired mitochondrial dynamics and removal of the damaged mitochondria in diabetic retinopathy

Abstract: IntroductionMitochondrial dynamic plays a major role in their quality control, and the damaged mitochondrial components are removed by autophagy. In diabetic retinopathy, mitochondrial fusion enzyme, mitofusin 2 (Mfn2), is downregulated and mitochondrial dynamic is disturbed resulting in depolarized and dysfunctional mitochondria. Our aim was to investigate the mechanism of inhibition of Mfn2, and its role in the removal of the damaged mitochondria, in diabetic retinopathy.MethodsUsing human retinal endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…These changes in diabetic patients and mice, which correlated with increased FIS1 and DRP1 levels, respectively [209,211], were also observed in aortic ECs cultured under hyperglycemic conditions [209]. Diabetic retinopathy is also associated with disturbed mitochondrial dynamics in human retinal ECs, where the acetylation of MFN2 protein plays a role [212]. However, hyperglycemia also affects other mitochondrial aspects, such as mtDNA repair mechanisms, which are impaired in hyperglycemia.…”
Section: Endothelial Mitochondrial Dysfunction In Diabetes Mellitusmentioning
confidence: 80%
“…These changes in diabetic patients and mice, which correlated with increased FIS1 and DRP1 levels, respectively [209,211], were also observed in aortic ECs cultured under hyperglycemic conditions [209]. Diabetic retinopathy is also associated with disturbed mitochondrial dynamics in human retinal ECs, where the acetylation of MFN2 protein plays a role [212]. However, hyperglycemia also affects other mitochondrial aspects, such as mtDNA repair mechanisms, which are impaired in hyperglycemia.…”
Section: Endothelial Mitochondrial Dysfunction In Diabetes Mellitusmentioning
confidence: 80%
“…Acetylphosphate, as a marker of mitochondrial activity, is considered a metabolic intermediate in the generation of citric acid cycle precursors and often mediates nonenzymatic acetylation ( 57 ). Previous studies revealed that acetylation of proteins such as mitofusin 2 ( 58 ), histones ( 59 ), and P65 ( 60 ) contributes to the development of DR. Our study suggested that acetylphosphate may be a risk factor for DR and the acetylation it mediates holds promise as a potential focus for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction is linked to various ocular diseases, including autosomal dominant optic atrophy [85], Leber's hereditary optic neuropathy [86], glaucoma [87], age-related macular degeneration (AMD) [88], and diabetic retinopathy (DR) [89]. It is known that inflammation can be triggered by oxidative stress caused by mitochondrial damage [90].…”
Section: Discussionmentioning
confidence: 99%